Living on the edge : the realities of welfare in America - Rank, Mark R. (Columbia University Press, 1994)
In this compelling look at the lives of welfare recipients, Mark Robert Rank shatters many of the myths commonly associated with the system and its participants. Living on the Edge considers three questions: Why do people turn to welfare? What is it like to survive on these programs? And what can we as a society do to address this critical issue? Based on ten years of research, the book follows individuals and families as they apply for and live on public aid and eventually leave the system. Rank's chronicle of their day-to-day experiences reveals the many sacrifices and crises that tax ordinary people in extraordinary ways. Beginning with a history of welfare from Roosevelt to Clinton, he focuses on AFDC and the Food Stamp program. He then describes the backgrounds of the recipients, their hopes for the future and attitudes toward welfare, their daily routines and problems, their work behavior, and the effect of welfare on family dynamics. Living on the Edge reveals the experiences of female-headed families, married couples, single men and women, and the elderly. Interviews, extensive data, and Rank's firsthand observations of the welfare system puncture the stereotypes of assumed laziness and apathy. By concentrating on a wide range of individuals and families, Rank depicts a side of the welfare experience rarely seen and dispels the myth that only the urban underclass - the center of most policy debate - struggles on welfare. Rank's juxtaposition of numbers and faces alerts us to the fact that welfare recipients have much in common with the rest of us. His frank analysis allows us to see beyond the common biases to the fundamental constraints and forces in our society that push so many people to life on the edge.